Substrate effect on the swelling and water sorption of Nafion nanomembrans - Abuin, Graciela Carmen (2012)
Swelling and sorption of water, from the vapour phase, by thin (100–1000 nm) and ultra-thin (<100 nm) Nafion nanomembranes deposited on several surfaces were determined using quartz crystal micro-balance and environmental ellipsometric porosimetry techniques. The water uptake at room temperature, measured as the number of water molecules per ionic group in the polymer, is much lower than that observed in bulky Nafion 117 membranes. Water sorption by supported nanofilms was found to be independent of film thickness, but it depends on substrate nature. Aging due to slow relaxation of the polymer microstructure is also discussed. Results are relevant for modelling the three-phase region of proton exchange membrane fuel cells, where a thin Nafion film covers the carbon supported catalyst nanoparticles.